An Effective and Robust Method for Unauthorized Reader Detection Based on Tag's Energy. (7th October 2022) - Cao, Ziwen; Xie, Jinxing; Wang, Siye; Zhang, Yanfang; Cui, Yue; Jiang, Shang; Jin, Biao
Abstract : With the rapid development of the Internet of Things, ultra-high frequency (UHF) passive radio frequency identification (RFID) technology plays a vital role in various fields. UHF RFID faces unauthorized access attacks due to its long identification distance. Unauthorized readers can hide within a certain distance and use standard commands to read or modify tags. However, existing methods require additional equipment or are susceptible to environmental influences. In this paper, we make a novel attempt to counterattack unauthorized access. We propose a new method for Unauthorized Reader Detection based on Tag's Energy, called URDTE, to detect unauthorized readers by observing the energy of the tag. The competitive advantage of URDTE is that it is fully compatible with the RFID standard EPCglobal Gen 2, which makes it more applicable and scalable in practice. Besides, it takes the electrical energy stored in a tag's resistor-capacitor (RC) circuit as the detection principle, which is robust to environmental changes such as tag position, communication distance, and transmit power. We implement URDTE using commercial off-the-shelf (COTS) RFID devices without requiring firmware or hardware modifications. Extensive experiments show that URDTE can detect unauthorized readers with an accuracy of up to 99%.